Dapur Bergerak Sdn. Bhd / Mohd Farhan Izaihan Izaimi... [et al.] - Izaimi, Mohd Farhan Izaihan Bin; Anthony, Mark; Mohd Hasnan, Mohd Azfar Syafiq Bin; Maimin, Siti Suharah Binti; Syed Abd. Kassim, Sh.Qasnoradilah Bt. (2012)
The name of our company is Dapur Bergerak Sdn.Bhd. Our business is based on partnership which includes 5 persons who have certain qualification in business management and wide knowledge about Malaysian foods. We have chosen to open ‘In-Truck Kiosk’ which sell Malaysian Foods. We have chosen to open this business as a fact that ‘iMalaysia’ concept has been accepted by Malaysian since there is variety of people in the country. The concept of ‘1 Malaysia’ has been introduced by our current Prime Minister of Malaysia Datuk Seri Mohd Najib Bin Tun Abd Razak as to unite our people which come in various race , religion and culture. As related, we will use the concept of T Malaysia’ in our product as to promote the diversity of taste and unique shape of the Malaysian Tradition foods. ‘Unique Malaysia ‘was the name that called by other foreign countries because of its unique diversity of religion, culture and even foods. For foods, we serve food like ketupat (malay) , Roti Canai (indian) , Asam fish (chinese), Hinava (Kadazan-dusun) , Sagol ( Bajau ) , Ambuyat (brunei). We choosen the food from these races because it is the main race in Peninsular Malaysia and majority ethnic Sabah. Furthermore, our kiosk will move from one destination to one destination ( around Kota Kinabalu area which covers Indah Permai , University Apartment 1 & 2 , Teluk Likas and Waterfront near Anjung Senja) from 4.00 pm to 8.00 pm depends on the available stock. Our products are fresh and were cooked in the truck. Our ‘in-truck’ kiosk also served beverage such as Teh Tarik , Es Cendol, Kopi Kaw and much more. Most important is that our business will be the first ever moving kiosk in Malaysia that served Malaysian Food which will be the new market for the entire entrepreneur out there.